Kebijakan Penanggulangan Kejahatan Studi Terhadap Resolusi Kongres PBB VIII/1990 Tentang Computer-Related Crime - Bahiej, Ahmad; Ach. Tahir, Ach. Tahir (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
The research aims at exploring and finding the fact on implementation  of  resolution  of  the  Nation  Union  Congress VIII/1990  on  Computer-related  Crime  at  State  Islamic University  of  Sunan  Kalijaga.  It  is  significant  to  know  what extent  the  university  responds  to  national  and  international issues on development of cyber crime. The university, the oldest institution  of  islamic  studies  in  Indonesia,  has  moralistic responsibility  for  encouraging  the  government  in  implanting awareness  on  development  and  danger  of  cyber  crime  for people, in particular for the university’s lectureres, students, and administrative  officers.  It  is  a  field  research  strengthened  by library  data  and  based  on  normatively -empirically-qualitatively legal approach. Its objects are curriculum, regul ations, deans or vice  deans  of  academic  affairs,  Centre  for  Computer  and Information  System  of  State  Islamic  University  of  Sunan Kalijaga,  and  libraries  around  the  university.  The  data  are collected  through  depth  interwiew  with  the  rector  or  vice rectors,  deans or vice deans, director of the centre, chairman of libraries,  and  several  communities  of  hackers.  In  addition,  the data collection is strengthened by spreading questionnaires to the university’s students in deal with students’ behaviors on internet.